(3QSGFd GdeMbb GdTjN eQJVi GdCfUGQj GdGSJUMGHs - (3GdORahdj GdCfUGQj, eQJVi Hf eMeO Cejf, J (B1281 (3g`s ((3GdeTgO GdeYXes)
(3ChdgG (B:s
.. (3aj JNUjU GSJUMGH MGd GdYbd HGSJUMGH Gdfaj hGdHQGAI HCf GdKGHJ HGdYbd bO jchf YOejG hbO jchf hLhOjG adG hLg ddJNUjU hPde deG YQaJ ef Cf GdLGd GdeSJfO Edi GdYbd (B..s
(3BNQgG (B:s
... (3EdG Cf JTNjU SdGeJgG ef GdCUhd GdMGceI YdjgG djS hXjaI cd CMO adGHO ef bOQI GdebdO Ydi JTNjU GdMGce ef GdCUhd (B.. (3CUd GdGSJUMGH hYOegG (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\201s
(3GdPQjYI (B16\1505s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs